Efficiently Delivering Online Services over Integrated Infrastructure - Viswanathan, Raajay; Calder, Matt; Akella, Aditya; Mahajan, Ratul; Padhye, Jitendra; Liu, Hongqiang Harry; Padhye, Jitu (USENIX - Advanced Computing Systems Association, 2016)
We present Footprint, a system for delivering online services in the “integrated” setting, where the same provider operates multiple elements of the infrastructure (e.g., proxies, data centers, and the wide area network). Such integration can boost system efficiency and performance by finely modulating how traffic enters and traverses the infrastructure. But fully realizing its benefits requires managing complex dynamics of service workloads. For instance, when a group of users are directed to a new proxy, their ongoing sessions continue to arrive at the old proxy, and this load at the old proxy declines gradually. Footprint harnesses such dynamics using a high-fidelity model that is also efficient to solve. Simulations based on a partial deployment of Footprint in Microsoft’s infrastructure show that, compared to the current method, it can carry at least 50% more traffic and reduce user delays by at least 30%.